Potential relationship between passive plantar flexor stiffness and sprint performance in sprinters - Takahashi, C.; Suga, T.; Ueno, H.; Miyake, Y.; Otsuka, M.; Terada, M.; Nagano, A.; Isaka, I. (Physical Therapy in Sport, 2018)
Objective: To investigate the relationship between passive planter flexor stiffness and sprint performance in sprinters. Design: Cross-sectional study. Participants: Fifty well-trained male sprinters (age: 20.7±1.9 years, height: 175.6±4.9cm, weight: 66.7±5.1kg) were participated in this study. Their best personal times in a 100-m sprint ranged from 10.22 to 11.86s (mean, 11.12±0.43s). Methods: Passive stiffness of the plantar flexors measured using a dynamometer system. Passive stiffness during passive dorsiflexion was calculated from the slope of the linear portion of the torque-angle curve. Results: Plantar flexor passive stiffness was significantly correlated with personal best 100-m sprint time (r=-0.334, P=0.018). Conclusion: The present findings suggest that although the relationship between plantar flexor passive stiffness and personal best 100-m sprint time was relatively minimal, a higher plantar flexor passive stiffness may be a potential factor for achieving superior sprint performance in sprinters. Therefore, in the clinical setting, measurement of passive planter flexor stiffness may be useful for assessing sprint performance.